Biosynthesis of non-sulfated high-molecular-weight glycosaminoglycans and specific-sized oligosaccharides. (1st November 2022) - Hu, Litao; Wang, Yang; Hu, Yunxiao; Yin, Juyi; Wang, Lingling; Du, Guocheng; Chen, Jian; Kang, Zhen
Abstract: Non-sulfated forms of glycosaminoglycans (NSGAGs) including hyaluronan, chondroitin and heparosan with high-molecular-weight (HMW) are extensively used biomaterials, while NSGAGs oligosaccharides display strong bioactivities. However, microbial production of HMW-NSGAGs and oligosaccharides with specific size are always challenging. Here, a membrane shield strategy was developed to produce HMW-NSGAGs by recruiting type II NSGAG synthases in Corynebacterium glutamicum . By enhancing precursor supplies and reinforcing cell membrane, the MWs of hyaluronan, heparosan and chondroitin reached 4100 kDa, 3000 kDa and 2400 kDa, respectively. In parallel, a synchronized depolymerization-polymerization strategy was developed by co-expressing NSGAGs synthases and lyases. With cell membrane as a filter, we achieved the direct biosynthesis of NSGAGs tetrasaccharides and disaccharides. The titers of chondroitin, hyaluronan and heparosan tetrasaccharides and disaccharides reached 10.9 g L −1, 12.1 g L −1 and 5.8 g L −1, respectively. The strategies developed here should also be applicable to the biosynthesis of other polysaccharides. Graphical abstract: Unlabelled Image